An outbreak of Gargaphia torresi in bean crop in Alagoas state - Silva, Cleonor C. A. da; Barbosa, Sérgio M. de Lima (Pesquisa Agropecuaria Brasileira, 2014)
The occurrence of Gargaphia torresi (Lima 1922) in outbreak, injuring bean crop in Santana do Ipanema County Alagoas State, Brazil, is reported for the first time. The nature of its damage causes serious decline in production.